Potentials of bio-adsorbent prepared from coconut fibre in mitigation of pollution from tanning effluent - Mst Sharmin Aktar; Md Saidur Rahman Shakil; Fatema Tuj-Zohra (Cleaner Engineering and Technology, 2023)
This study deals with the reduction of diverse pollutant including chromium from tanning effluent by using bio-adsorbent developed from a naturally available coconut fibre. The experiment examined varying several parameters like pH (3.0-5.0), adsorbent dosage (1.5-4.0 g L-1), time (5-360 min), concentration (131.62-248.19 ppm), and temperature (298-338 K). Pyrolyzed activated coconut fibre powder (PACF) was prepared and characterized by Fourier Transformed Infrared Spectroscopy (FTIR) and Field Emission Scanning Electron Microscopy (FESEM) to determine the functional groups and surface morphology. The FTIR spectra of PACF confirmed broader cellulosic O-H stretching vibration peak at 3404 and 3387 cm-1 before and after adsorption. To narrate the adsorption equilibrium, the Langmuir and Freundlich isotherms were used and the maximum adsorption capacity was found 81.30 mg g-1. The kinetics of adsorption process was studied by using pseudo-first-order and pseudo-second-order models, where pseudo-second-order kinetic model was found better fitted with adsorption data. The reduction of pollution, such as chromium content (66.53%), total dissolved solids (TDS) (63.77%), biochemical oxygen demand (BOD) (58.19%), chemical oxygen demand (COD) (61.69%), and electrical conductivity (EC) (64.39%), from chrome tanning effluents was achieved. Regeneration of adsorbent was simple by desorption with HCl and neutralized with NaOH solution. The coconut fiber is naturally available, non-toxic, biocompatible and biodegradable that was unexplored for removal of chromium from tanning effluent. This bioadsorbent support circular economy by using biological waste that has both the advantages of water treatment and waste management. The developed bio-adsorbent has good efficiency to remove chromium(III) and other pollutants from tanning effluent.